2016
DOI: 10.1186/s12885-016-2555-z
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 expression promotes esophageal squamous cell carcinoma proliferation and worsens the prognosis

Abstract: BackgroundThe chemokine CXCL12 and its corresponding receptor CXCR4 are key players in the development of several cancers. Therefore, we hypothesized that there is a functional causality between CXCL12 expression and tumor progression in patients with esophageal squamous cell carcinoma (ESCC).MethodsWe performed an immunohistochemical analysis in 79 consecutive patients with ESCC. We performed in vitro and in vivo cell proliferation assays using ESCC cell lines and a newly established transfectant stably overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…Overexpression of CXCR4 has been implicated in tumour metastasis and has been found to metastasise to tissues with a high concentration of CXCL12, such as lungs, liver and bone marrow (Balkwill, ). Interestingly, immunohistochemistry on 79 oesophageal squamous cell carcinoma tissue samples found that the proliferation index was higher in patients samples with higher expression of CXCR4 or CXCL12 (Uchi et al ., ). This effect on cell proliferation was also observed in vitro where inhibition of CXCR4 suppressed proliferation of synovial sarcoma cell lines (Kimura et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Overexpression of CXCR4 has been implicated in tumour metastasis and has been found to metastasise to tissues with a high concentration of CXCL12, such as lungs, liver and bone marrow (Balkwill, ). Interestingly, immunohistochemistry on 79 oesophageal squamous cell carcinoma tissue samples found that the proliferation index was higher in patients samples with higher expression of CXCR4 or CXCL12 (Uchi et al ., ). This effect on cell proliferation was also observed in vitro where inhibition of CXCR4 suppressed proliferation of synovial sarcoma cell lines (Kimura et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Recent reports evaluating biopsy samples of esophageal cancer tumors demonstrated a high intensity of CXCR4 receptor expression [26,27]. Additionally, chemokine receptor expression was a predictor of poor recurrence-free and overall survival [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CXCR4 plays a key role in the self-renewal of CSCs in drug-resistant NSCLC [201]. Due to the powerful protumor activities of CXCL12/CXCR4 axis, numerous studies have consistently shown that their expression is associated with poor prognosis for patients in esophageal cancer [202], acute myelogenous leukemia [203], BC [204,205], HCC [206], and NSCLC [207]. In addition, CXCR4 expression correlates with the degree of tumor infiltration and promotes a more aggressive phenotype in papillary thyroid carcinoma [208], and is also a negative prognostic marker for response to chemotherapy in NHL [209].…”
Section: Cxcl12/cxcr4mentioning
confidence: 99%